Comparing the efficacy of duloxetine and nortriptyline in alleviating the symptoms of functional dyspepsia – a randomized clinical trial - Banihashem, Seyed Shahab; Mofatioshieh, Seyedeh Mahsa; Rastegar, Reyhaneh; Sadeghi, Amir (Frontiers in Psychiatry, 2024)
Aim: To compare the efficacy of Duloxetine and Nortriptyline in alleviating the symptoms of severity, anxiety, depression and quality of life in patients with functional dyspepsia (FD).We conducted a single-blinded 3-month trial of Duloxetine 20 to 30 mg daily in 20 patients and Nortriptyline 25 mg daily in 25 FD patients. The primary outcome measure was the severity of FD symptoms by Gastrointestinal symptoms rating scale. Secondary measures included Hamilton Anxiety Rating Scale, Hamilton Depression Rating Scale, and Nepean Dyspepsia Index. the patients were measured in 3 stages.Results: 45 patients with FD with a mean age of 37.18±10.62 years participated in the study. The severity of symptoms was significantly lower in the Nortriptyline group than in the Duloxetine group after three months (p=0.031). The level of anxiety (p=0.049), depression (p=0.045) and quality of life (p=0.046) improved significantly after three months in the Duloxetine group compared to Nortriptyline. Mediation analysis using linear regression revealed a significant mediator role for anxiety. This mediation analysis revealed a 21.13% reduction in anxiety in the Duloxetine group.While both medications demonstrated efficacy, Nortriptyline appeared to be superior in symptom reduction. Duloxetine exhibited more advantages compared to Nortriptyline in addressing anxiety and depression and enhancing the overall quality of life. Also, Duloxetine may have a noteworthy impact, contributing to a 20% reduction in FD symptoms by lowering anxiety levels.